Energy-Oriented Economic Evaluation of Phase Shifters Utilizing Risk-Adjusted Lifecycle Cost Analysis - Hui Cai; Wanchun Qi; Zhuyi Peng; Jie Zou; Wentao Sun; Ying Zhu; Xingning Han (Energies)
In response to the growing need for efficient and sustainable energy systems, phase shifters are pivotal in enhancing the flexibility and reliability of power grids while facilitating the integration of renewable energy sources. This paper conducts a comprehensive economic evaluation of various phase shifter technologies, including symmetrical dual-core mechanical phase shifters, electronic phase shifters, and controllable phase shifters, using a lifecycle cost (LCC) analysis framework tailored for the energy sector. The assessment employs probability distributions and Monte Carlo simulation methods to analyze their economic performance, considering key energy-related cost factors such as initial investment, operational efficiency, maintenance, and decommissioning. An uncertainty analysis is introduced to refine the accuracy of LCC calculations, while sensitivity analysis highlights the influence of cost fluctuations—especially in initial investment and operating costs—on overall performance. The results reveal that while large-capacity phase shifters involve higher upfront costs, their superior operational efficiency and lower long-term unit costs can provide substantial economic advantages for sustainable energy applications. These findings offer valuable insights for optimizing energy equipment selection and guiding investment decisions in the transition toward greener and more resilient energy systems.